2020
DOI: 10.3390/molecules25153508
|View full text |Cite
|
Sign up to set email alerts
|

Fused 1,5-Naphthyridines: Synthetic Tools and Applications

Abstract: Heterocyclic nitrogen compounds, including fused 1,5-naphthyridines, have versatile applications in the fields of synthetic organic chemistry and play an important role in the field of medicinal chemistry, as many of them have a wide range of biological activities. In this review, a wide range of synthetic protocols for the construction of this scaffold are presented. For example, Friedländer, Skraup, Semmlere-Wolff, and hetero-Diels-Alder, among others, are well known classical synthetic protocols used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Until now, research studies revealed their impressive antimicrobial [ 6 , 8 , 177 ], antifungal [ 6 , 8 , 111 , 112 ], and antimycobacterial [ 10 , 178 ] effects, and some of them displayed activity superior or comparable to those presented by chloramphenicol [ 112 ], amphotericin B [ 115 ], and rifampin [ 124 ]—drugs used in standard therapeutic regimens. Moreover, naphthyridines were shown to present significant properties including antiinfectious: antiviral [ 11 , 24 , 50 , 51 ], antiparasitic [ 9 , 176 ], and antimalarial [ 113 ]; anticancer [ 5 , 6 , 23 , 35 ]; influencing cardiovascular system: hypotensive [ 16 , 27 ], cardioprotective [ 43 , 44 ]; neurological: sedative [ 94 ], analgesic [ 15 ], anticonvulsant [ 78 ], stimulating neuritogenesis [ 188 ]; psychotropic: antianxiety [ 97 ], antidepressant [ 29 , 97 ]; and affecting immune system: anti-inflammatory [ 7 , 56 , 57 ], immunosuppressant [ 48 , 49 , 50 ]. The spectrum of activity of naturally-derived naphthyridines is wide, thus these compounds are undeniably fascinating subjects of research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, research studies revealed their impressive antimicrobial [ 6 , 8 , 177 ], antifungal [ 6 , 8 , 111 , 112 ], and antimycobacterial [ 10 , 178 ] effects, and some of them displayed activity superior or comparable to those presented by chloramphenicol [ 112 ], amphotericin B [ 115 ], and rifampin [ 124 ]—drugs used in standard therapeutic regimens. Moreover, naphthyridines were shown to present significant properties including antiinfectious: antiviral [ 11 , 24 , 50 , 51 ], antiparasitic [ 9 , 176 ], and antimalarial [ 113 ]; anticancer [ 5 , 6 , 23 , 35 ]; influencing cardiovascular system: hypotensive [ 16 , 27 ], cardioprotective [ 43 , 44 ]; neurological: sedative [ 94 ], analgesic [ 15 ], anticonvulsant [ 78 ], stimulating neuritogenesis [ 188 ]; psychotropic: antianxiety [ 97 ], antidepressant [ 29 , 97 ]; and affecting immune system: anti-inflammatory [ 7 , 56 , 57 ], immunosuppressant [ 48 , 49 , 50 ]. The spectrum of activity of naturally-derived naphthyridines is wide, thus these compounds are undeniably fascinating subjects of research.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products—cimiciduphytine 14 and eburnane derivatives 15 ( Figure 4 )—were evaluated as natural painkillers and antihypertensive agents, which could be used in cerebral circulation disturbance therapy [ 16 ].…”
Section: Naturally Occurring Naphthyridine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…e naphthyridine framework exists in a number of natural and synthetic substances with various chemical reactivities and exceptional physicochemical [1] and biological properties [2,3], which include anticancer, [4] HIV-I inhibitor, [5] anticonvulsant, [6] antimalarial [7], and anti-Alzheimer [8]. Among the six possible (1,5−, 1,6−, 1,7−, 1,8−, 2,6−, and 2,7−) isomeric pyridopyridines, [9,10] 1,8-naphthyridines and their derivatives have diverse potential in clinical and medicinal chemistry due to their anti-inflammatory, [11] antimalarial, [12] antihypertensive, [13] gastric antisecretory, [14] antiplatelet aggregation, [15] AChE inhibitory, [16] antihistaminic, [2] antimicrobial [17,18], and anticancer [19][20][21] activities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The naphthyridine (Figure 1) ring has gained attention, becoming an important pharmacophore in the discovery of new biological agents due to its attractive biological activities [29]. In this sense, several naphthyridine derivatives present good pharmacological activity with low toxicity [30]. In addition, among the most cited applications related to 1,8naphthyridines are antiparasitic [31,32], antibacterial [33,34], and antiviral [35][36][37] activities.…”
Section: Introductionmentioning
confidence: 99%